1994
DOI: 10.1002/yea.320101009
|View full text |Cite
|
Sign up to set email alerts
|

Expression and in vivo determination of firefly luciferase as gene reporter in Saccharomyces cerevisiae

Abstract: The LUC gene coding for Photinus pyralis firefly luciferase was cloned in different yeast episomal plasmids in order to assess its possibilities as an in vivo reporter gene. Activity of the enzyme in transformed cells in vivo was measured by following light emission and assay conditions optimized in intact cells, with regard to oxygen concentration, temperature, cell concentration in assay mixtures and external ATP concentration. Among the factors tested, light emission was drastically influenced by the extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Other studies have indicated that permeabilization of samples prior to reading increases the sensitivity of the luciferase assay (Vieites et al, 1994;McNabb et al, 2005;Liu et al, 2008). Permeabilization of yeast cultures using proprietary detergents has been All measurements represent the mean AE SD for at least three independent trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have indicated that permeabilization of samples prior to reading increases the sensitivity of the luciferase assay (Vieites et al, 1994;McNabb et al, 2005;Liu et al, 2008). Permeabilization of yeast cultures using proprietary detergents has been All measurements represent the mean AE SD for at least three independent trials.…”
Section: Resultsmentioning
confidence: 99%
“…Advances to luciferase systems -most notably, a transition from in vitro to in vivo assays (Leskinen et al, 2003) -has been a watershed event in promoter-reporter systems. Detection remains inexpensive (a major advantage of the original detection method), while retaining large, accurate and quantifiable dynamic ranges without the variability reported between in vitro samplings (Vieites et al, 1994;Tauriainen et al, 1999). Most importantly, measurement of in vivo bioluminescence can be taken quickly, accurately and in one-step (Michelini et al, 2005), without the additional lysis step commonly required of other luciferase assays (McNabb et al, 2005;Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…So far, the detection of luciferase activity of living yeast cells has required a somewhat elaborate protocol, which has included centrifugation and cell resuspension steps (Vieites et al, 1994). In this study we wanted to simplify the luciferase activity measurement in yeast and especially avoid centrifugation-resuspension steps, since they are incompatible with high-throughput screening (HTS) applications.…”
Section: Resultsmentioning
confidence: 99%
“…There are only few reports of the use of the firefly luciferase as a reporter gene in yeast and even fewer are the reports of its use in vivo. Vieites et al (1994) found that the in vivo light emission from firefly luciferase in yeast is highest when the pH of the assay medium is below 3, which is probably the result of an increase in the amount of uncharged D-luciferin that facilitates its diffusion through the cytoplasmic membrane and cell wall. Above pH 3 the light emission dramatically decreased and at pH 5 the signal was rather weak.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction was started with 10 mM fumarate in an incubation mixture of 100 mM Tris (pH 9.0), 0.1% Triton X-100, 4 U of malate dehydrogenase (Boehringer) per ml, and 1 mM APAD for 5 min at 37°C. Luciferase activity was measured in intact cells and in lysates as described by Vieites et al (47). Cultured cells were centrifuged, washed twice with distilled water, and resuspended in sterile water to be kept in 10 mM phosphate buffer (pH 7.0) at 4°C until used.…”
Section: Methodsmentioning
confidence: 99%